Geological characterisation of the Bamboesberg Member within the Molteno-Indwe coalfield, Eastern Cape Province, South Africa - Lenhardt, Nils (University of Pretoria, 2024)
Dissertation (MSc (Geology))--University of Pretoria, 2024.